Pengembangan Lembar Kerja Siswa Ilmu Pengetahuan Sosial Berbasis Inkuiri Terbimbing untuk Siswa SMP - Ina Mahmuda; Anindya Fajarini (heritage, 2020)
Abstract                This research aims to produce a student worksheet social studies guided inquiry-based in class VIII of SMP Negeri 1 Jember. The research method used is research and development (R&D). This research adopted a 4-D development model with three stages namely; define, design, and development. The sample of this research is class VIII-A and class VIII-B. The research subjects consisted of four experts namely; material experts, design experts, linguists, and social studies teachers. Data collection techniques using a questionnaire. Data were analyzed using descriptive analysis techniques. The results of the validation from the expert team are; 1) material experts with a percentage score of 80%; 2) design experts with a percentage score of 82.67%; 3) linguists with a percentage score of 85.3%; 4) Social studies teacher with a percentage score of 82%. Limited test results obtained by students' responses with a percentage of 91%. The results of the field test obtained student responses with a percentage of 83.16%. Based on the validity criteria and student response criteria the effectiveness of the student worksheet social studies guided inquiry-based is valid and suitable to use without revision. The cognitive learning outcomes of 28 students of class VIII-A have completely reached the KKM value, with a percentage of 87.5%. Whereas 4 students of class VIII-A failed to achieve the KKM value, with a percentage of 12.5%. The cognitive learning outcomes of five VIII-B students completely reached the KKM value, with a percentage of 83.3%. While one VIII-B student failed to achieve the KKM value, with a percentage of 16.7%. Based on the classical completeness criteria class VIII A and B have completely reached the KKM value. So, it can be concluded that student worksheet social studies guided inquiry-based is suitable and effectively for used social studies learning at SMP Negeri 1 Jember. Abstrak Penelitian ini betujuan untuk menghasilkan lembar kerja siswa (LKS) ilmu pengetahuan sosial berbasis inkuiri terbimbing pada kelas VIII SMP Negeri 1 Jember. Metode penelitian yang digunakan yaitu Research and Development (R&D). Penelitian ini mengadopsi model pengembangan 4-D dengan tiga tahapan yaitu; define, design, dan development. Sampel dari penelitian ini yaitu kelas VIII A dan kelas VIII B. Subyek penelitian terdiri dari empat ahli, yakni ahli materi, ahli desain, ahli bahasa, dan guru IPS. Teknik pengumpulan data menggunakan angket. Data dianalisis menggunakan teknik analisis deskriptif. Hasil validasi dari tim ahli yaitu; 1) ahli materi dengan prosentase skor 80%; 2) ahli desain dengan prosentase skor 82.67%; 3) ahli bahasa dengan prosentase skor 85,3%; 4) guru IPS dengan prosentase skor 82%. Hasil uji terbatas diperoleh respon siswa dengan prosentase 91%. Hasil uji lapangan diperoleh respon siswa dengan prosentase 83,16%. Berdasarkan kriteria kevalidan dan kriteria respon siswa keefektifan LKS IPS berbasis inkuiri terbimbing dinyatakan valid dan layak digunakan tanpa revisi. Hasil belajar kognitif 28 siswa kelas VIII A tuntas mencapai nilai KKM, dengan prosentase 87,5 %. Sedangkan 4 siswa kelas VIII A gagal mencapai nilai KKM, dengan prosentase 12,5%. Hasil belajar kognitif 5 siswa kelas VIII B tuntas mencapai nilai KKM, dengan prosentase 83,3%. Sedangkan 1 siswa kelas VIII B gagal mencapai nilai KKM, dengan prosentase 16,7%. Berdasarkan kriteria ketuntasan klasikal kelas VIII A dan B telah tuntas mencapai nilai KKM. Jadi, dapat disimpulkan bahwa LKS IPS berbasis inkuiri terbimbing layak dan efektif digunakan untuk pembelajaran IPS SMP Negeri 1 Jember.   Kata Kunci: Lembar Kerja Siswa, Ilmu Pengetahuan Sosial, dan Inkuiri Terbimbing